2022
DOI: 10.1186/s12934-022-01888-0
|View full text |Cite
|
Sign up to set email alerts
|

Cheese whey supports high riboflavin synthesis by the engineered strains of the flavinogenic yeast Candida famata

Abstract: Background Riboflavin is a precursor of FMN and FAD which act as coenzymes of numerous enzymes. Riboflavin is an important biotechnological commodity with annual market sales exceeding nine billion US dollars. It is used primarily as a component of feed premixes, a food colorant, a component of multivitamin mixtures and medicines. Currently, industrial riboflavin production uses the bacterium, Bacillus subtilis, and the filamentous fungus, Ashbya gossypii, and utilizes glucose and/or oils as ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recently, we have shown that the engineered strains of C. famata are characterized by robust growth on lactose and cheese whey and riboflavin overproduction in these media. Expression of SEF1 transcription activator under control of LAC4 promoter increased riboflavin production on whey (Ruchala et al, 2022). We decided to check if introduction of SEF1 under control of lactose‐induced LAC4 promoter activates FMN synthesis in strains with overexpressed FMN1 gene.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we have shown that the engineered strains of C. famata are characterized by robust growth on lactose and cheese whey and riboflavin overproduction in these media. Expression of SEF1 transcription activator under control of LAC4 promoter increased riboflavin production on whey (Ruchala et al, 2022). We decided to check if introduction of SEF1 under control of lactose‐induced LAC4 promoter activates FMN synthesis in strains with overexpressed FMN1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…Reciprocally, the D. hansenii FMN1 gene was expressed under control of C. famata TEF1 promoter in the strain AF‐4/pLAC4‐SEF1 containing additional copy of SEF1 gene under the control of LAC4 promoter (Ruchala et al, 2022). The presence of the introduced gene was confirmed by PCR using corresponding pairs of primers (Supporting Information: Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations